A TRIBUTE TO THEODORE ROSZAK. THE MAKING OF A COUNTERCULTURE - BORBÉLY, Ştefan (Studia Universitatis Babeș-Bolyai Philologia, 2019)
A Tribute to Theodore Roszak. The Making of a Counterculture. The American professor Theodore Roszak (1933 – 2011) is generally credited with the invention of the term “counterculture”, although his seminal book from 1969, The Making of a Counter Culture spells the two words separately. To us, today it seems to be the work of a rather cautious, but pioneering sociologist, who acknowledges indeed the legitimacy of the student revolts of the Sixties but at the same time tries to distance himself from their heat with the cool objectivity of the academic observer. REZUMAT. Omagiu lui Theodore Roszak. Facerea unei contraculturi. Profesorul American Theodore Roszak (1933 – 2011) este îndeobşte creditat cu inventarea cuvântului “contracultură”, deşi cartea sa de referinţă din 1969, The Making of a Counter Culture (Facerea contraculturii) ortografiază separat cele două cuvinte. Astăzi, cartea ne apare ca fiind opera de pionierat a unui sociolog mai degrabă circumspect, care admite, e drept, legitimitatea revoltelor studenţeşti din anii 1960, dar se şi distanţează de incandescenţa lor cu obiectivitatea rece a unui observator academic. Cuvinte cheie: contracultură, anii 1960, Theodore Roszak.